Penentuan Kondisi Operasi Elektroplating Krom yang Ramah Lingkungan - Perdana, Sanjaya Putra; Priambodo, Anton; Munarsyah, Tryas; Pustaka, Bagas Winagandi; Widayanto, Tri (Institut Teknologi Bandung, 2017)
Electroplating is a method of surface coating by using an electrolytic process. The technique was aimed to improve its corrosion resistance and to obtain an aesthetic and decorative appearance. In the experiments, metalic chrome was used to be electrodeposited on to copper substrates. A thin layer of electrodeposited chrome was expected to be on the surface of working electrode. The working electrode was copper plate (3 mm thickness) with a length of 2 cm and a width of 1 cm. Polarization experiments were carried out at various electrolyte concentrations of 5 g/l, 10 g/l and 15g/l. Electrolytes were prepared using chromium chloride because it is more environmentally friendly. Polarization experiments were carried out by applying potentials range between 0.1V ando 3.5V at intervals of 0.1 V. The electrical current responses were recorded so that polarization curves were obtained. Electrochemical parameters such as potential and current for electroplating were determined based on the polarization curves. The electrical currents used for electroplating experiments were 80% of  limiting current and the limiting current for  each concentration. The results of electroplating experiments were then analyzed using digital microscopy. The results obtained at a concentration of 5 g/l and 10 g/l show more uniform and smoother surfaces. Deposited chrome obtained at the concentration of 15 g/l was non uniform thickness. It can be concluded that a relatively good deposited chrome was obtained at the electrolyte concentration of 5 g/l at a current of 18.2 mA which shows more uniform and dense plated chrome.